Narrating, Doing, Experiencing Nordic Folkloristic Perspectives - Palmenelt, Ulf (Studia Fennica Folkloristica, 2006)
How do people tell of experiences, things and events that mean a lot to them and are unforgettable? Eight Nordic folklorists here examine personal experience stories and the way they are narrated in an attempt to gain an understanding of the people behind them and to reveal how these people handle their history, their lives and their cultural memory. All the articles are based on interviews and narrator-researcher collaboration. The stories tell about birth, sickness and miraculous cures, intergenerational relations, war, and matters not normally talked about. The analyses complement one another and the work may be used as a university course book.